Lactic acid bacteria administration from Jember tempeh (Indonesia) as a probiotic candidate in intestinal physiology and histology of mice strain Balb-C - SITI NUR AZIZAH; ROSIDA ROSIDA; AMALIYAH NURUL HIDAYAH; ANIES ROHMAN DWIJAYANTI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Azizah SN, Rosida, Hidayah AN, Dwijayanti AR. 2023. Lactic acid bacteria administration from Jember tempeh (Indonesia) as a probiotic candidate in intestinal physiology and histology of mice strain Balb-C. Biodiversitas 24: 6969-6978. The lactic acid bacteria of tempeh have been studied for their potential as a probiotic with highly beneficial effects on health. This study aimed to investigate the potential of lactic acid bacteria from Jember tempeh on white mice's intestinal physiology and histology. The highest population of lactic acid bacteria isolated from three Jember tempeh types with GYP solid media was found in the Kaliwates tempeh (TK) at 2.74 × 108 cells/ml. According to the purification and lactic acid activity, the LAB isolates, encoded as TA.1, TB.1, TK.1, TK.2, and TK.4 are all probiotic candidates. All isolates obtained the optimum growth time at the 15th hour in TA.1 and TB.1 isolates, the 6th hour in TK.1 and TK.2 isolates, and the 8th hour in TK.4 isolate. The administration of LAB probiotics from Jember tempeh on the weight gain of mice presents a sig value of 0.38>0.05, which means an insignificant effect on the weight gain among the group. The solid feces condition of mice was also similar within groups. The administration of LAB probiotics on the intestinal histology of mice presents a sig value of 0.028<0.05, which means a significant effect within groups, showing a similar condition between the consortium administration group and the normal group. Groups TA.1, TB.1, TK.1, TK.4 and control (Lactobacillus acidophillus) had the same intestinal histology, namely partial necrosis. The administration of LAB probiotics from Jember tempeh can also reduce the population of Salmonella and Escherichia coli bacteria more effectively than without the probiotics. Thus, a good treatment group used as a probiotic candidate is a consortium.